Parents Awareness of Vision Care Issues in Children Ages Four to Six - Ng, Lisa W.; Jones, Deborah A. (Canadian Journal of Optometry, 2021)
Previous studies have shown that less than 15% of children receive an eye examination before age six. A reason for this lack of vision care may be (related to) poor parent education. Using a questionnaire, we surveyed parents with a child between ages four and six to investigate their awareness of child vision care. Results indicate that most parents (73%) took their child for an exam before age six, but few parents (5%) took their child at the (CAO recommended) age six months. Parents therefore have a high degree of vision awareness, but further have education is necessary to increase the percentage of children obtaining eye examination at an earlier age.